Dietary Phosphorus and Ambulatory Blood Pressure in African Americans: The Jackson Heart Study. (10th August 2018) - Olivo, Robert E; Hale, Sarah L; Diamantidis, Clarissa J; Bhavsar, Nrupen A; Tyson, Crystal C; Tucker, Katherine L; Carithers, Teresa C; Kestenbaum, Bryan; Muntner, Paul; Tanner, Rikki M; Booth, John N; Mwasongwe, Stanford E; et al.
Abstract: BACKGROUND: Higher dietary phosphorus is associated with left ventricular hypertrophy and mortality, which are blood pressure (BP)-related outcomes. For this reason, we hypothesized that dietary phosphorus may be associated with adverse clinic and ambulatory BP patterns. METHODS: Our study included 973 African American adults enrolled in the Jackson Heart Study (2000–2004) with 24-hour ambulatory BP monitoring (ABPM) data at baseline. We quantified dietary phosphorus from a validated Food Frequency Questionnaire as follows: (i) absolute daily intake, (ii) ratio of phosphorus-to-protein intake, (iii) phosphorus density, and (iv) energy-adjusted phosphorus intake. Using multivariable linear regression, we determined associations between dietary phosphorus intake and systolic blood pressure (SBP), diastolic blood pressure (DBP), and pulse pressure in clinic and over daytime, nighttime, and 24-hour periods from ABPM. Extent of nocturnal BP dipping was also assessed. Using logistic regression, we modeled relationships between dietary phosphorus intake and clinically relevant qualitative BP phenotypes, such as masked, sustained, or white-coat hypertension and normotension. RESULTS: There were no statistically significant associations between phosphorus intake and SBP or pulse pressure in adjusted models. Most metrics of higher phosphorus intake were associated with lower daytime, nighttime, and clinic DBP. Higher phosphorus intake was not associated with clinic or ABPM-defined hypertension overall, but most metrics of higher phosphorus intake were associated with lower odds of sustained hypertension compared to sustained normotension, white-coat hypertension, and masked hypertension. There were no associations between dietary phosphorus and nocturnal BP dipping. CONCLUSIONS: These data do not support a role for higher phosphorus intake and higher BP in African Americans.